093 Tracheostomy in plw motor neuron disease – prolonged survival with continuous ventilation via a cuffed tube. Issue 6 (27th May 2022) - Ramsay, Michelle; Kaltsakas, George; Howard, Leo; Sheridan, Shauna; Marino, Phillip; Murphy, Patrick; Hart, Nick; Howard, Robin
Abstract : The role of tracheostomy in the management of ventilatory failure due to motor neuron disease (MND) remains controversial. Although it is an effective alternative to non-invasive ventilation (NIV) in supporting ventilation, the risk of prolonged survival in the face of reduced quality of life is a concern. We present 25 patients living with (plw) MND who underwent tracheostomy. There were 16 males, the mean age was 64.0 yrs (36–83), 13 patients underwent tracheostomy prior to the diagnosis and could not be weaned, the mean duration of tracheostomy to death or December 2019 was 3.4 yrs (0.2–8.7). 19 patients required continuous ventilation using a permanently cuffed tube. All the patients became entirely dependant, and 8 had limited or no communication despite eye gaze or environmental control systems. 14 patients were in care homes and 11 required 24 hr support at home. Several patients expressed their desire to maintain invasive ventilatory support despite inevitable and progressively increasing dependence. Many plw MND become dependent on invasive ventilatory support before the diagnosis is established and may live for prolonged periods following tracheostomy despite total dependence. The use of tra- cheostomy in MND raises issues about the balance of patient autonomy, resource allocation and the role of medical professionals. robinhoward@nhs.net